Class II major histocompatibility complex antigen expression on peripheral blood monocytes in patients with inflammatory bowel disease. Issue 4 (April 1994) - Gardiner, K R; Crockard, A D; Halliday, M I; Rowlands, B J
Abstract : Macrophage major histocompatibility complex (MHC) class II antigen expression is associated with defective antigen presentation to T lymphocytes in animals and is predictive of patient outcome after major trauma or sepsis. In this study, class II antigen (HLA-DR and DQ) expression on peripheral blood monocytes was investigated in patients with inflammatory bowel disease in relation to disease activity and outcome. The percentage positivity and fluorescent intensity of expression of HLA-DR and DQ antigens on monocytes were determined in whole blood samples using dual colour immunofluorescence labelling and flow cytometry. Disease activity was assessed using clinical and laboratory indices. There was no significant difference in percentage positivity or fluorescent intensity of class II antigen expression between patients with Crohn's disease, those with ulcerative colitis, and healthy volunteers. The percentage of monocytes displaying HLA-DR positivity was significantly decreased in patients with active ulcerative colitis (active %: 49.5 (5.6); inactive %: 78.9 (6.9); p = 0.01). Data expressed as mean (SEM). In patients requiring surgical resection of diseased bowel, the percentage of monocytes displaying HLA-DR positivity (51.9 (4.0) %) was significantly reduced compared with patients receiving medical treatment alone (81.1 (3.5) %; p < 0.001). Reduced monocyte HLA-DR expression is therefore associated with disease activity and seems to predict outcome in patients with inflammatory bowel disease.